Historical data and standardized catch rates of porbeagle (Lamna nasus) caught as bycatch of the Spanish surface longline fishery targeting swordfish (Xiphias gladius) in the Atlantic Ocean - Mejuto-García, Jaime; Ortiz-de-Urbina-Gutiérrez; José María; García-Cortés, Blanca; Ramos-Cartelle, Ana (2010)
Standardized catch rates of porbeagle shark (Lamna nasus) were obtained from 15 458 trip observations of surface longline targeting swordfish, during the period 1986-2007. In roughly 12% of these trips at least one individual belonging to this species was found. Because of the low prevalence of this species in this fishery, standardized CPUE was developed using GLM procedures assuming a delta-lognormal distribution error. A base case run and alternate runs were done. The base case run suggests a moderately decreasing trend between 1986 and 1996, a period of stability until the year 2000 and a slight increase thereafter. The results obtained using only the traditional style longline with some data restrictions indicate that the trend was substantially stable from 1986-2000. The results obtained show standardized CPUE trends that were very similar for the whole time series, regardless of the type of analysis conducted. Scientific estimations of annual catches for the period 1997-2008 have also been updated No